2020
DOI: 10.3329/bjch.v44i1.49684
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever: Clinical Characteristics of A Tertiary Care Hospital Study

Abstract: Background: Incidence of dengue infection has increased worldwide and has become a significant public health concern. Clinical suspicion based on the frequency of symptoms is very important for early diagnosis. Objectives: To observe the clinical characteristics of serologically confirmed hospitalized cases of dengue fever. Material and Methods: This cross-sectional study was done among admitted children with dengue infection in Dhaka Shishu (Children) Hospital from July 2018 to October 2018. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In our study dengue fever, both severe and non-severe, were observed in were observed in male's patients as compared to female's patients. These findings are in accordance with the previous study who reported more cases of dengue infection in males as compared to females 13 . Another study carried out by HOSSAIN MZ et al reported more cases of dengue infection in males as compared to females 8 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study dengue fever, both severe and non-severe, were observed in were observed in male's patients as compared to female's patients. These findings are in accordance with the previous study who reported more cases of dengue infection in males as compared to females 13 . Another study carried out by HOSSAIN MZ et al reported more cases of dengue infection in males as compared to females 8 .…”
Section: Discussionsupporting
confidence: 94%
“…The most common clinical manifestations in this research were headache in 81.4% patients, myalgia in 62.3%, and nausea in 62.3% and vomiting in 62.3% patients. Apart from fever, these three symptoms have been listed as the most prevalent both by national and international researchers 13,17 .…”
Section: Discussionmentioning
confidence: 99%